Perceptions of Disability: Implications for Educational Attention of Students of the National University of Costa Rica - Fontana-Hernández, Angélica (2018)
This article was written within the research project “Perceptions and realities of addressing educational needs: a proposal for professional development and its implementation at the National University of Costa Rica.” The research approach was qualitative, and the main objective was to analyze perceptions and constructions of disability and their implications to address educational needs. Qualitative research techniques were applied, such as questionnaire, incomplete phrases, and imagery association. In the study, 427 academic staff participated. The results pointed out that the constructions about disability emerge from the perception of disability as an individual and person-centered condition within a traditional approach. The results showed the importance of implementing a pedagogical strategy with the academic staff of the institution; it is a strategy about the principles of inclusive education and the inclusion of persons with disabilities for specific purposes in the university academic practice and inclusive pedagogical practices.